Oral changes in patients submitted to chemotherapy treatment (Research, Society and Development, 2021)
Chemotherapy cancer treatment is invariably responsible for triggering oral changes resulting from the decrease in the patient's immune response. Chemotherapy is one of the most used and effective forms of cancer treatment, however it triggers countless side effects in all organic systems, including in the oral cavity. Among them, mucositis stands out, one of the causes of greatest discomfort for the patient, also responsible for an instability in his quality of life. It is essential that the cancer patient seek a dental surgeon so that there is a prevention, treatment and monitoring of these changes aiming at an improvement in the quality of life before, during and after chemotherapy or any other cancer treatment. Therefore, it is extremely important to determine the main oral changes related to chemotherapy treatment, as well as to assess the prevalence of each change and its toxic effects.